Analysis of Fiscal Policy in the Management of the National Budget in Indonesia - Usman Usman; Wartoyo Wartoyo (Peradaban Journal of Economic and Business, 2024)
The study aims to analyze fiscal policy in managing the state budget of Indonesia. The method employed is descriptive analysis, which involves explaining and describing information from both oral and written sources obtained through literature studies. The findings indicate that Indonesia's fiscal policy leans towards an expansionary approach, leading to a deficit in the state budget. Additionally, the government has initiated the export of downstream commodities with high added value to boost state revenue. Furthermore, the adoption of zero-based budgeting has been implemented to minimize state spending. These strategies are believed to enhance the management of the state budget. Penelitian ini bertujuan untuk menganalisis kebijakan fiskal dalam mengelola anggaran negara Indonesia. Metode yang digunakan adalah analisis deskriptif, yang melibatkan penjelasan dan deskripsi informasi dari sumber-sumber lisan dan tertulis yang diperoleh melalui studi literatur. Temuan menunjukkan bahwa kebijakan fiskal Indonesia cenderung mengarah pada pendekatan ekspansionis, yang mengakibatkan defisit dalam anggaran negara. Selain itu, pemerintah telah memulai ekspor komoditas hilir dengan nilai tambah tinggi untuk meningkatkan pendapatan negara. Selain itu, penerapan anggaran berbasis nol juga telah dilakukan untuk meminimalkan pengeluaran negara. Strategi-strategi ini diyakini dapat meningkatkan pengelolaan anggaran negara.